Comparing the Use of Risk-influencing Production Inputs and Experimentally Measured Risk Attitude: Do the Decisions of Indonesian Small-scale Rubber Farmers Match? - Stefan Moser; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2017)
This article compares the use of risk-increasing and risk-reducing production inputs with the experimentally measured risk attitudes of farmers. For this purpose, a Just-Pope production function indicates production inputs' influence on output risk, and a Holt-Laury lottery is used to measure farmers' risk attitudes. We then test whether more risk averse farmers use more risk-reducing and
Keywords: 330